Evaluating Canola Varietal Response to Calcium Chloride and Sodium Chloride-Induced Salt Stress - Attaullah (International Journal of Applied Research and Sustainable Sciences, 2024)
Treatment of canola genotypes (HC-10, KSM-75, C-05, WY-02, WY-01, HC-09, and SAWABI-C) with NaCl (0, 100 mM) and CaCl2(0, 100 mg/l) to find the stress tolerance genotype was investigated. In the current study, two types of salt stresses NaCl and CaCl2 were applied in a complete randomized design in Petri dishes and their combination, and the data was collected from chlorophyll contents. And growth parameters like shoot weight, root weight, and biomass. The findings of the study indicated that a significant difference was found in treatments of NaCl and CA for all the genotypes of canola in germination traits. The results revealed that HC-09 is lower affected by salt from calcium chloride and genotype HC-10 is less affected by NaCl stress. In chlorophyll content, the genotype HC-09 has higher results in chlorophyll a, b, a/b, and carotenoids on the application of both NaCl 100 mM/l and CaCl2 100 mg/l. It is concluded that the genotype HC-09 has been shown more tolerance in each stress and indicates higher values while the genotype HC-10 has also tolerance in some traits.